2020
DOI: 10.1266/ggs.19-00056
|View full text |Cite
|
Sign up to set email alerts
|

<i>De novo</i> transcriptome analysis reveals an unperturbed transcriptome under high cadmium conditions in the Cd-hypertolerant fern <i>Athyrium yokoscense</i>

Abstract: Athyrium yokoscense shows strong tolerance to cadmium exposure, even at levels that are many times greater than the toxic levels in ordinary plants. To determine the mechanism of Cd tolerance in A. yokoscense, we grew these plants under high Cd conditions and observed the tissue-specific accumulation of Cd and generation of reactive oxygen species, which is one of the major physiological responses to Cd stress. Fuchsin staining indicated the existence of a casparian strip in A. yokoscense roots, which may part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…In the roots of A. yokoscense, the existence of a Casparian strip has been suggested (Ukai et al 2020). This might restrict Cd intrusion into the central region.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In the roots of A. yokoscense, the existence of a Casparian strip has been suggested (Ukai et al 2020). This might restrict Cd intrusion into the central region.…”
Section: Discussionmentioning
confidence: 98%
“…OsNramp5 is Nramp family transporter located on the cell membrane of Oryza sativa, which is involved in Mn and Fe transport in their roots. We have reported the cDNA dataset that was established by RNA-seq analysis of A. yokoscense cells (Ukai et al 2020). This report has revealed that A. yokoscense has eight genes encoding proteins…”
Section: A Yokoscense Nramp5 Takes Up CD Into Rice Transformant Cellsmentioning
confidence: 99%
“…Based on the Illumina HiSeq sequencing platform, the transcriptomes of roots and shoots of Athyrium yokoscense ( Ukai et al, 2020 ), young leaves of Asplenium nidus , young leaves of Asplenium komarovii ( Zhang et al, 2019 ) and sexual reproduction and apogamy of Adiantum reniforme gametophytes ( Fu & Chen, 2019 ) were studied, and 35,681, 89,741, 77,912, 333,352, 264,791 transcripts were obtained, respectively. The sequencing read length of the Illumina HiSeq is short, the mRNAs need to be broken into short fragments before sequencing, and the complete transcripts can be obtained only by splicing.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Ukai et al 22 performed an RNA-seq analysis of A. yokoscense sporophytes exposed or not to Cd and found few significant changes in the A. yokoscense Article transcriptome, even under high Cd conditions. These results imply that most genes involved in Cd tolerance and accumulation may be constitutively expressed in A. yokoscense, regardless of the presence or absence of Cd, like the case of Arabidopsis halleri, a facultative Cd and Zn hyperaccumulator.…”
Section: Discussionmentioning
confidence: 99%
“…These results imply that most genes involved in Cd tolerance and accumulation may be constitutively expressed in A. yokoscense, regardless of the presence or absence of Cd, like the case of Arabidopsis halleri, a facultative Cd and Zn hyperaccumulator. 23 Interestingly, however, Ukai et al 22 also found that the level of an NPF ortholog, which is a putative nitrate transporter gene, doubled in response to Cd stress in the roots. For plants, owing to its low availability, nitrogen is the critical limiting element.…”
Section: Discussionmentioning
confidence: 99%